Compelling God : theories of prayer in Anglo-Saxon England - Clark, Stephanie, 1975- (University of Toronto Press, 2018)
"While prayer is generally understood as "communion with God" modern forms of spirituality prefer "communion" that is non-petitionary and wordless. This preference has unduly influenced modern scholarship on historic methods of prayer particularly concerning Anglo-Saxon spirituality. In Compelling God, Stephanie Clark examines the relationship between prayer, gift giving, the self, and community in Anglo-Saxon England. Clark's analysis of the works of Bede, Ælfric, and Alfred utilizes anthropologic and economic theories of exchange in order to reveal the ritualized, gift-giving relationship with God that Anglo-Saxon prayer espoused. Anglo-Saxon prayer therefore should be considered not merely within the usual context of contemplation, rumination, and meditation but also within the context of gift exchange, offering, and sacrifice. Compelling God allows us to see how practices of prayer were at the centre of social connections through which Anglo-Saxons conceptualized a sense of their own personal and communal identity."--! Provided by publisher
Keywords: Bede, -- the Venerable, Saint, -- 673-735.; Alfred, -- King of England, -- 849-899.; Aelfric, -- Abbot of Eynsham.; Bede, -- the Venerable, Saint, -- 673-735; Alfred, -- King of England, -- 849-899; Aelfric, -- Abbot of Eynsham; English literature -- Old English, ca. 450-1100 -- History and criticism.; Christian literature, Latin (Medieval and modern) -- England -- History and criticism.; Prayer -- Christianity -- History.; Prayers, Early Christian.; Prayer in literature.; Littérature anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique.; Littérature chrétienne latine médiévale et moderne -- Angleterre -- Histoire et critique.; Prière -- Christianisme -- Histoire.; Prières chrétiennes primitives.; Prière dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Christian literature, Latin (Medieval and modern); English literature -- Old English; Prayer -- Christianity; Prayer in literature; Prayers, Early Christian; England; 450-1100; Criticism, interpretation, etc.; History